Functional outcome of tibial plateau fracture managed conservatively - Rijal, Anubhav; Rajthala, Aashish (International Journal of Research in Orthopaedics, 2020)
Background: Tibial plateau fractures involve the articular surface of the proximal tibia. They account for approximately 1% of adult fractures. A number of articles have been published regarding tibial plateau fracture management. Interestingly excellent results have been published concluding not all fractures of the tibial plateau require surgery and not all displaced intra-articular fractures need to be reduced surgically. In this method we used conservative method to restore normal joint anatomy, joint stability, and functional motion and avoid complications. Methods: This study design is prospective study including forty randomly selected cases of diagnosed tibial plateau fracture presented in Orthopaedic department of tertiary referral centre over 18 months period and treated with conservative method. The patients then were followed up and evaluation of outcome was analyzed as per modified Rasmussen clinical criteria and radiological criteria at six months. Results: In this study, tibial plateau fracture was seen more in patients of age group 31-40 (35%). Mean age being 41.25 years. There were 28 (70%) male and 12 (30%) female. Road traffic accident comprises the majority of cases (75%). Regarding radiological outcome, 41.5% had excellent result, 34.3% had good result, 8.5% had fair result and 15.7% had poor result. 84% had acceptable outcome. The Rasmussen’s functional outcome at final follow up was 46% patients had excellent result, 30% had good result, 12% had fair result and 12% had poor result. 88% had acceptable clinical outcome. Conclusions: Conservative management of tibial plateau is still a reliable, inexpensive and alternative treatment option with favourable functional outcome.